Graphite saturable absorber for Q switched fiber laser - Yuzaile, Yushazlina R.; Awang, Noor Azura; Zakaria, Zahariah; Zalkepali, Noor U.H.H; Latif, Amirah A.; Azmi, Atiqah N.; Abdul Hadi, Fatin Shaqira (Science Publishing Corporation, 2018)
This paper reported a successful demonstration on Q-switched fiber laser by using graphite as saturable absorber (SA). The graphite is deposited on the fiber ferrule through a simple mechanical exfoliation method. The modulation depth of the graphite SA is 19.2% with a saturation intensity of 85 MW/cm². The maximum achievable pulse repetition rates and pulse width are 42.41 kHz and 3.40 μs respec-tively. Meanwhile, its optical signal-to-noise ratio is about 50.81 dB. The Q-switched pulses have the maximum pulse energy of 5.84 nJ. These outcomes demonstrated that a stable output of passively Q-switched fiber laser is produced and can be applied for various optical fiber applications.